Peningkatan Kemampuan Guru PAI dalam Menyusun Laporan Penelitian Tindakan Kelas: Studi pada MGMP Kabupaten Lombok Barat - Sukman _Sukman (eL-HIKMAH: Jurnal Kajian dan Penelitian Pendidikan Islam, 2020)
One of the fundamental activities in teacher professional development is the development of teacher skills, especially in conducting classroom action research. For the teachers who are members of the MGMP PAI West Lombok Regency, the teacher's ability to conduct classroom action research is still low. For that, we need an effort that can be used as an alternative to improve this capability, one of the efforts is through training activities. The research subjects were teachers of Islamic Religious Education at MGMP PAI at SMK West Lombok Regency. This research was conducted in two cycles. Methods of data using observation and documentation techniques. data validation used in this action research is democratic validation, process, and dialogue. Data analysis was carried out by comparing the results in the initial conditions, the results of cycle I, the results of cycle II. From the results of the research and training conducted during these two cycles, there was a change in the preparation of classroom actions for teachers who are members of the MGMP PAI, West Lombok Regency.